Performance Analysis of Quantum Long Short-Term Memory (QLSTM) Models for TLKM Stock Price Prediction - Nasya Vhazira; Irmayatul Hikmah; Mas Aly Afandi (Forum Kerjasama Pendidikan Tinggi, 2026)
Stock price prediction is a challenging task due to its nonlinear, dynamic, and temporal characteristics, yet accurate forecasting models are crucial for decision-making in volatile stocks such as PT Telkom Indonesia Tbk (TLKM). Despite the rapid adoption of AI-based forecasting methods, several research gaps remain. Empirical studies on Quantum Long Short-Term Memory (QLSTM) are still relatively limited compared to classical LSTM variants, particularly for emerging market datasets. Existing research also tends to emphasize architectural comparisons rather than systematically analyzing training configurations. The joint effects of optimizer selection, epoch number, and hidden unit size on QLSTM performance have not been comprehensively evaluated, and many studies rely on limited evaluation metrics, reducing the strength of robustness assessment. To address these gaps, this study applies a QLSTM model to predict stock opening prices using historical time-series data and systematically evaluates the impact of different optimizers. The model is trained using Adam, Nadam, RMSprop, and SGD with epoch variations (50–250) and hidden units (8, 16, 32). Performance is measured using accuracy, MAE, MSE, RMSE, MAPE, and R² to ensure a comprehensive evaluation. The results indicate that adaptive optimizers consistently outperform SGD, with Adam providing the most stable and accurate predictions, highlighting the importance of optimizer choice and hyperparameter configuration in QLSTM-based stock forecasting.